2003
DOI: 10.1016/s0887-6177(02)00139-7
|View full text |Cite
|
Sign up to set email alerts
|

The electrophysiological effects of a brain injury on auditory memory functioning The QEEG correlates of impaired memory

Abstract: The effect of a brain injury on the quantitative EEG (QEEG) variables during an auditory memory activation condition was examined with 56 normal subjects and 85 mild traumatic brain-injured (MTBI) subjects. An analysis was conducted on the different response patterns of the two groups, the variables which were correlated with memory performance in the brain-injured group, and the variables which predicted the memory score for the combined two groups (normal and brain injured). The three conditions included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…The head injured group relative to controls had increased EEG amplitudes and amplitude variances particularly in the beta band, with no significant differences in relative power of the bands between the two groups. In other studies of long term effects, Thornton (1999Thornton ( , 2000Thornton ( , 2003 reported significantly lowered values in the TBI group (with a post injury time frame ranging from \1 to 43 years), compared to normal controls in SCC and phase beta2 (32-64 Hz) relations under eyes closed condition (1999), auditory and visual attention (2000) and listening to paragraphs condition (2003), predominantly from frontal locations. Previous research (Thatcher et al 1989) with the eyes closed condition had not examined these relations.…”
Section: Frequency Parametersmentioning
confidence: 77%
See 4 more Smart Citations
“…The head injured group relative to controls had increased EEG amplitudes and amplitude variances particularly in the beta band, with no significant differences in relative power of the bands between the two groups. In other studies of long term effects, Thornton (1999Thornton ( , 2000Thornton ( , 2003 reported significantly lowered values in the TBI group (with a post injury time frame ranging from \1 to 43 years), compared to normal controls in SCC and phase beta2 (32-64 Hz) relations under eyes closed condition (1999), auditory and visual attention (2000) and listening to paragraphs condition (2003), predominantly from frontal locations. Previous research (Thatcher et al 1989) with the eyes closed condition had not examined these relations.…”
Section: Frequency Parametersmentioning
confidence: 77%
“…Thus, in the previous two cognitive activation studies cited (Randolph and Miller 1988;Thornton 2003), the TBI subject shows increased beta (amplitudes and/or relative power) compared to normals. The three eyes closed comparisons reported specific decreases in beta (20.5-36 Hz) and high alpha (10.5-13.5 Hz; Tebano et al 1988), alpha (8-13 Hz;Thatcher et al 1989), and increases in low alpha (8-10 Hz; Tebano et al 1988) and theta (4-8 Hz; Thornton 1999).…”
Section: Frequency Parametersmentioning
confidence: 86%
See 3 more Smart Citations